Same label, different patients: Health-workers’ understanding of the label ‘critical illness’ - Mkumbo, Elibariki; Willows, Tamara Mulenga; Onyango, Onesmus; Khalid, Karima; Maiba, John; Schell, Carl Otto; Oliwa, Jacquie; McKnight, Jacob; Baker, Tim (Frontiers in Health Services, 2023)
Background During the course of patients’ sickness, some become critically ill, and identifying them is the first important step to be able to manage the illness. During the course of care provision, health workers sometimes use the term ‘critical illness’ as a label when referring to their patient's condition, and the label is then used as a basis for communication and care provision. Their understanding of this label will therefore have a profound impact on the identification and management of patients. This study aimed to determine how Kenyan and Tanzanian health workers understand the label ‘critical illness’. Methods A total of 10 hospitals—five in Kenya and five in Tanzania—were visited. In-depth interviews were conducted with 30 nurses and physicians from different departments in the hospitals who had experience in providing care for sick patients. We conducted a thematic analysis of the translated and transcribed interviews, synthesized findings and developed an overarching set of themes which captured healthcare workers’ understandings of the label ‘critical illness’. Results Overall, there does not appear to be a unified understanding of the label ‘critical illness’ among health workers. Health workers understand the label to refer to patients in four thematic ways: (1) those in a life-threatening state; (2) those with certain diagnoses; (3) those receiving care in certain locations; and (4) those in need of a certain level of care. Conclusion There is a lack of a unified understanding about the label ‘critical illness’ among health workers in Tanzania and Kenya. This potentially hampers communication and the selection of patients for urgent life-saving care. A recently proposed definition, “a state of ill health with vital organ dysfunction, a high risk of imminent death if care is not provided and the potential for reversibility”, could be useful for improving communication and care.